A Computational Study of the Protein-Ligand Interactions in CDK2 Inhibitors: Using Quantum Mechanics/Molecular Mechanics Interaction Energy as a Predictor of the Biological Activity (2007)
ABSTRACT: We report a combined quantum mechanics/molecular mechanics (QM/MM) study to determine the protein-ligand interaction energy between CDK2 (cyclin-dependent kinase 2) and five inhibitors with the N2 -substituted 6-cyclohexylmethoxypurine scaffold. The computational results in this work show that the QM/MM interaction energy is strongly correlated to the biological activity and can be used as a predictor, at least within a family of substrates. A detailed analysis of the protein-ligand structures obtained from molecular dynamics simulations shows specific interactions within the active site that, in some cases, have not been reported before to our knowledge. The computed interaction energy gauges the strength of protein-ligand interactions. Finally, energy decomposition and multiple regression analyses were performed to check the contribution of the electrostatic and van der Waals energies to the total interaction energy and to show the capabilities of the computational model to identify new potent inhibitors.